SVM strategy with duty-offset component injection for a three-phase/level PFC rectifier based on current sector control - Y. Kumsuwan (2018)
© 2016, Institution of Engineering and Technology. All rights reserved. This paper presents a simple applied space vector modulation (SVM) strategy using a duty-offset component injection for three-phase/level power factor correction rectifier, based on current sector control. In the proposed strategy, the duty cycle equations are determined by utilizing the calculated switching time method in order to generate the duty cycle signals based on a seven-segment switching sequence principle is fully described. A duty-offset equation is presented in order to change the duty cycle signals to new duty cycle signals for the three-phase/level rectifier. Compared with the conventional discontinuous SVM scheme, the main advantage of the proposed continuous SVM (CSVM) strategy is the reduction of the common-mode voltage leads to a further reduction in leakage current, which is between the neutral point of capacitors and the neutral point of the grid connected to the ground. The effectiveness of the proposed CSVM strategy has been verified though computer simulation results.